2018
DOI: 10.1039/c8sm00895g
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of force generation by spreading platelets

Abstract: In order to gain more insight into the role of human platelets for blood clot formation, here we investigate the dynamics of force generation by platelet spreading onto elastic substrates of variable stiffness. Despite their small size, platelets generate high and rapidly varying traction forces on their extracellular environment, which we reconstruct with adapted implementations of Fourier transform traction cytometry. We find that while the final spread area is reached within a few minutes, the build-up of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
122
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(134 citation statements)
references
References 55 publications
(90 reference statements)
12
122
0
Order By: Relevance
“…2,3 When adhering to a substrate, they start to spread to a flat shape, reaching about 30 to 40 mm 2 in area with a height of 100 nm or less. [4][5][6] The activation is initiated via several pathways such as physical triggers, e.g. shear forces, or chemical cues, such as ADP or thrombin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 When adhering to a substrate, they start to spread to a flat shape, reaching about 30 to 40 mm 2 in area with a height of 100 nm or less. [4][5][6] The activation is initiated via several pathways such as physical triggers, e.g. shear forces, or chemical cues, such as ADP or thrombin.…”
Section: Introductionmentioning
confidence: 99%
“…The contraction of single blood platelets or small clots in no-flow environments has been thoroughly characterized by different techniques, including micropost arrays, 13,14 atomic force microscopy (AFM), 15 traction force microscopy (TFM) 6,16 and, most recently, tension sensors. 17 The measured forces depend greatly on the method used and can reach some hundreds of nN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using polyacrylamide gels with a tunable elastic modulus, Qiu et al observed that fibrinogen functionalized stiffer gels (elastic modulus of 5.0 kPa and 50 kPa) promoted platelet adhesion, spreading, and activation, while on soft gels (0.5 kPa) platelet function was abrogated and was dependent on Rac1 and actomyosin activity. Subsequent TFM experiments on substrates of higher elastic modulus (from 19 kPa up to 83 kPa) revealed that traction forces generated by fully activated platelets were independent of the matrix stiffness . Although platelets generated isotropic contractile traction forces, at the steady state, assessment of force localization showed that these were largest at the periphery of platelets, while the traction force was focused near the platelet granulomere.…”
Section: Traction Force Measurementsmentioning
confidence: 99%
“…During hemostasis, the ter- revealed that traction forces generated by fully activated platelets were independent of the matrix stiffness. 84 Although platelets generated isotropic contractile traction forces, at the steady state, assessment of force localization showed that these were largest at the periphery of platelets, while the traction force was focused near the platelet granulomere.…”
Section: Tfm On Hydrogel Substratesmentioning
confidence: 99%